Learning from trade through innovation: Causal link between imports, exports and innovation in Spanish microdata - Jože P. Damijan; Črt Kostevc (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
The paper explores the learning from trade hypothesis. Standardized research approach searchs for learning effects from trade focusing solely on exports, whereby firm's learning effects are accounted in the firm of total factor productivity improvements. In contrast, this papers defines a firm learning from trade in tfirms of introduction of either new products or processes induced by its import and export links with foreign markets. By using microdata for a large sample of Spanish firms, including data on innovation and trade, we find clear sequencing between imports, exports and innovation. The results suggest that firms learn primarily from import links, which enables them to innovate products and processes and to dress up for starting to export. In a sequence, exporting may enable firms to introduce further innovations. These positive learning effects from trade, however, seem to be limited to small and partially medium firms only. On the other side, firms that are closer to the relevant technological frontier seem to benefit more from trading activities in tfirms of innovation than the technological laggard firms.
Keywords: D24; F14; F21; 330; firm heterogeneity; innovation; exports; imports; matching; Außenhandelswirtschaft; Export; Import; Lernende Organisation; Innovation; Produktivität; Spanien